The Characterization of Interferon Regulatory Factor 2 (IRF-2) Gene From Maleo (Macrocephalon Maleo S. Müller 1846) Tuva Village Gumbasa Sub-District Sigi Regency Central Sulawesi and it’s Utilization as Learning Media - Ashari, Abdul; Budiarsa, I Made; Astija, Astija (Jurnal Riset Pendidikan MIPA, 2018)
IRF-2 is a member of the interferon regulatory transcription factor (IRF) which encodes interferon regulating factors. The study aimed to describe the character of the Interferon Regulatory Factor 2 (IRF-2) gene sequence from maleo and provide an experimental module about molecular genetic methods. This study used descriptive methods. Genetic data were obtained by using the molecular method through three stages of DNA isolation, DNA amplification, and sequencing. Alignment is done using Clustal X in the MEGA6 program. Phylogeny tree constructed by Neighbor-Joining algorithm and Juke-Cantor evolution's model from program MEGA6. The sample consisted of 0,3 ml blood from two individual maleo and species of Megapode group as a comparison that was obtained from GenBank. The results of the analysis from 612 bp of IRF-2 genes identified with the composition of the nucleotide base of 23.1% T, 20.8% C, 35.1% A and 21.0% G. IRF-2 gene sequence of nucleotide composition was rich in adenine (A). Analysis of IRF-2 gene sequences phylogeny tree topology tree produced good enough and has aggregated species from Megapodiidae family. Moreover, the validation suggested that the practical guide book in this study were ‘eligible’ to be used as learning media.